Sustainability of Salt Tolerant Varieties to Counter Climate Change Under Semiarid Saline Conditions of Pali, Rajasthan: Assessment of Salt tolerant wheat varieties - Singh, Dheeraj; Chaudhary, Mahendra Kumar; Kuri, Bhola Ram; Kumar, Chandan; Tetarwal, Arvind Singh (Journal of Soil Salinity and Water Quality, 2023)
Expanding problems of soil salinity have become serious issues of concern in arid zone of Pali district as they affect productivity and threaten the very sustainability of agriculture. Looking to this problem CAZRI KVK made an attempt to access and improve the productivity of small farms in Pali by organizing 300 front line demonstrations (FLD) in its selected villages during 2017-20 using salt tolerant variety of wheat. Under this programme, quality seeds of improved varieties of wheat of the area were distributed to the identified farmers. In order to harness the synergy between technologies and the community participation, special emphasis was given to build farmer's capacity to produce quality produce with enhanced yield. Fine-tuning of the production technology based on the location specific conditions and resources available with the farmers enhanced the adoption rate. The results indicate higher additional returns and effective yield under demonstrations which were due to improved variety, scientific proven technology, non-monetary factors, timely operations of crop cultivation and scientific monitoring.  From an initial start of 300 farmers the variety and innovation spread to 140 villages covering 790 hectares of area.